Description of chest pain patients in a Norwegian emergency department. (2nd January 2019) - Bjørnsen, Lars Petter; Naess-Pleym, Lars Eide; Dale, Jostein; Grenne, Bjørnar; Wiseth, Rune
Abstract: Objectives . Chest pain is one of the most frequent chief complaints in patients admitted to the emergency department (ED). No study has evaluated this patient population in Norway. The aim of the present study was to describe the diagnoses and logistics of chest pain patients admitted to the ED at a Norwegian university hospital. Design . Data were collected from all patients referred to the ED at St. Olav's Hospital-Trondheim University Hospital in 2015. Patients presenting at the ED with a chief complaint of chest pain based on the Rapid Emergency Triage and Treatment System were included in this study. Results . In the study period, 22, 403 patients were admitted to the ED. Chest pain was the second most common chief complaint (11%), only exceeded by acute abdominal pain (18%). Among the chest pain patients, 12% had acute coronary syndrome (ACS) and 37% were diagnosed with non-specific chest pain. Gastrointestinal, musculoskeletal, and pulmonary conditions were less common, affecting 6%, 4%, and 4% of the patients, respectively. In total, 90% of the ED chest pain patients were handled by the Clinic of Cardiology. Conclusions . Chest pain was the second most common chief complaint among patients admitted to the ED, and most patients were handled by the Clinic of Cardiology. More than one-third of the patients received a cardiac diagnosis, but the largest group of patients was discharged with a diagnosis of non-specific chest pain. Other conditions managed by non-cardiac medical specialties were less common.